ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI POLA BILANGAN DITINJAU DARI GENDER - Siti Astria Harti; Adi Ihsan Imami (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The research was carried out with the aim of analyzing problem-solving abilities in junior high school students related to number pattern material in terms of gender. The method used is descriptive qualitative. The subject of the study was a class VIII student at one of the junior high schools in Karawang Regency in the odd semester of the 2022/2023 academic year. The procedure for data collection uses a test instrument that combines four indicators in the form of, understanding, planning, implementing planning, and reviewing processes and results in problem solving. The data analysis technique is to look at the test results of students and then categorize them on high, medium, and low criteria. The results showed that the mathematical problem-solving ability of female students was better with an average score of 80.76 in the high category than male students with an average score of 69.58 in the medium category. This can result in differences in students' ways of thinking, understanding, and solving problems.